Опыт использования диодного лазера при лечении хронического пульпита во временных зубах (Эндодонтия Today, 2020)
Treatment of pulpitis of immature deciduous teeth in children is a difficult task, since classical endodontic treatment is not possible. The preferred methods are vital pulpotomy and partial pulpectomy. The goal was to increase the effectiveness of treatment of pulpitis by pulpotomy of deciduous teeth with the introduction of the laser. In the clinic of child dentistry 25 children with chronic pulp (ICD-10 K04.03) formed in (n = 12) and immature (n = 16) teeth in age from 1,5 to 6 years were examined and sanitized. The treatment was effected by the method of vital pulpotomy using a diode laser of SiroLaser. This article describes a technique for treatment of chronic pulpitis in temporary teeth with a diode laser and the results of treatment a year later. The use of a diode laser in the clinic of child dentistry justified economically advantageous and is more refined alternative to existing methods of treatment of pulpitis in temporary teeth in children.